Superior long term outcome of patients with early transformation of non-Hodgkin lymphoma undergoing stem cell transplantation - Reddy, Nishitha (Clin Lymphoma Myeloma Leuk, 2012)
Transformed non-Hodgkin’s lymphoma arising from follicular lymphoma (TL) carries a poor prognosis with a median survival time after transformation reported to be around a year. Fifty one consecutive patients with TL received stem cell transplantation (SCT) between January 2000 and December 2010 (autologous [auto-SCT] 44, allogeneic SCT [allo-SCT] 7). Thirty six (70.5%) patients had an early transformation, defined as histological evidence of transformation at the time of initial diagnosis or transformation within one year of follicular lymphoma. Fifteen patients had early stage disease (29%) and 36 (71%) with advanced stage disease on presentation. At the time of analysis, 37 patients were alive with an estimated 5 year overall survival (OS) and event free survival (EFS) of 61.8% and 45% respectively. OS and EFS were not significantly different between types of transplant procedure. The major cause of transplant failure was disease recurrence, with estimated 2 year relapse rate of 37.4%. Importantly, early transformation was independently associated with improved OS (HR 3.29, p=0.028) and EFS (HR 2.49, p=0.029). Our results indicate that aggressive transplant approach should be considered upfront in patients with TL and emphasize the need to incorporate novel strategies (e.g. immunomodulation) early post-SCT to prevent relapses as disease recurrence remains the major cause of failure in heavily pre-treated patients.